2012
DOI: 10.1039/c2nr11573e
|View full text |Cite
|
Sign up to set email alerts
|

A highly stable, efficient visible-light driven water photoelectrolysis system using a nanocrystalline WO3 photoanode and a methane sulfonic acid electrolyte

Abstract: Nanostructuring of semiconductor films offers the potential means for producing photoelectrodes with improved minority charge carrier collection. Crucial to the effective operation of the photoelectrode is also the choice of a suitable electrolyte. The behaviour of the nanostructured WO(3) photoanodes in methane sulfonic acid solutions, which allow one to obtain large, perfectly stable visible-light driven water splitting photocurrents, is discussed. The important effect of the electrolyte concentration upon t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
109
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 105 publications
(115 citation statements)
references
References 12 publications
5
109
1
Order By: Relevance
“…Electrochemical impedance spectroscopy (EIS) is a powerful technique to characterize charge transfer processes in nanostructured WO 3 films. 49,50 Before reduction, two semi-circles are observed in the Nyquist plot ( Figure 5B), indicating two limiting charge transfer processes with distinct time constants (radii) in the as-prepared WO 3 nanoplate film. The first arc with the smaller radius is assigned to electron transport through the film, whereas the second arc with the larger radius is related to the interfacial charge transfer at the WO 3 -electrolyte interface.…”
Section: Resultsmentioning
confidence: 99%
“…Electrochemical impedance spectroscopy (EIS) is a powerful technique to characterize charge transfer processes in nanostructured WO 3 films. 49,50 Before reduction, two semi-circles are observed in the Nyquist plot ( Figure 5B), indicating two limiting charge transfer processes with distinct time constants (radii) in the as-prepared WO 3 nanoplate film. The first arc with the smaller radius is assigned to electron transport through the film, whereas the second arc with the larger radius is related to the interfacial charge transfer at the WO 3 -electrolyte interface.…”
Section: Resultsmentioning
confidence: 99%
“…Tungsten trioxide, WO 3 , an earth-abundant, oxidatively stable semiconductor, is one such material that could fulfill the role of photoanode. [14][15][16][17][18][19][20][21][22][23][24] In most deposition methods, the presence of oxygen vacancies serve as shallow electron donors and naturally dope the WO 3 n-type. 25 Its band gap of 2.6 eV is higher than ideal for the large band gap absorber in a tandem cell.…”
Section: Introductionmentioning
confidence: 99%
“…[31] Recently, we showed that, in contrast with most of acidic electrolytes (HClO 4 , H 2 SO 4 others), the methane-sulfonic acid supporting electrolyte does not undergo changes over the photoelectrolysis and insures stable long-term operation of a WO 3 photoanode. [34] In fact, Raman spectroscopic analyses of a 1 m CH 3 SO 3 H solution that had been used as water splitting electrolyte, with the WO 3 photo anode irradiated with high intensity light over 70 h, did not show any spectral changes. This makes an essential difference with respect to, e.g., the H 2 SO 4 electrolyte that under similar conditions underwent to a large extent a conversion into persulfuric acid.…”
mentioning
confidence: 98%